2020
DOI: 10.1016/j.foodhyd.2019.105258
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of egg white gel microstructure and its relationship with pepsin diffusivity

Abstract: Understanding the diffusion of digestive enzymes, particularly pepsin, in different food structures, is a key factor to better control protein digestion and absorption. This study aimed to investigate how protein-based food microstructure impacts pepsin diffusion. Two egg white gels (EWGs) of identical protein concentration (10%) but different structures were used as food models. The two different gel structures were prepared by heating liquid egg white at pH5 and pH9, respectively. Results showed that egg whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…The porous microstructure of the pH 5-EWG may enable diffusion of water as a result of the moisture concentration gradient (Fickian diffusion). As illustrated in Nyemb et al 19 and Somaratne et al, 34 interconnecting empty pores of the pH 5-EWG matrix served as pathways for diffusion of water that enters the egg gel matrix. In contrast to the pH 5-EWG matrix, a complex interplay between the concentration gradient of moisture and the polymer erosion due to acid and pepsin hydrolysis of the protein-gel matrix (non-Fickian diffusion) governed the water diffusion within the pH 9-EWG.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 98%
See 2 more Smart Citations
“…The porous microstructure of the pH 5-EWG may enable diffusion of water as a result of the moisture concentration gradient (Fickian diffusion). As illustrated in Nyemb et al 19 and Somaratne et al, 34 interconnecting empty pores of the pH 5-EWG matrix served as pathways for diffusion of water that enters the egg gel matrix. In contrast to the pH 5-EWG matrix, a complex interplay between the concentration gradient of moisture and the polymer erosion due to acid and pepsin hydrolysis of the protein-gel matrix (non-Fickian diffusion) governed the water diffusion within the pH 9-EWG.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 98%
“…Article by the compact and dense nature of pH 9-EWG 19,34 and the negligible initial acid content of the pH 9-EWG matrix.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme transport from the gastric juice to the protein gel has to be incorporated in the model. Several studies have already indicated the importance of diffusion of pepsin ( Thevenot et al., 2017 , Qi et al., 2017 , Somaratne et al., 2020 ), and how it is influenced via the protein gel microstructure via obstruction and decrease of free volume ( Axpe et al., 2019 ). The diffusion of pepsin, or fluorescent molecules of similar size, has been compared to several diffusion models, as reviewed by ( Masaro and Zhu, 1999 , Amsden, 2002 ).…”
Section: Models With Realistic Gastric Conditionsmentioning
confidence: 99%
“…egg white gels, whey protein gels, dairy gels etc.) on nutrient release during gastric digestion has extensively studied (Guo et al, 2015;Guo, Ye, Lad, Dalgleish, & Singh, 2014;Le Feunteun et al, 2014;Somaratne et al, 2019Somaratne et al, , 2020bSomaratne et al, , 2020c, the mechanism by which the diffusion of the gastric juice affects the mechanical disintegration of natural food matrices (i.e. fruits, vegetables etc.)…”
Section: Introductionmentioning
confidence: 99%